Optimalisasi Pendidikan Kesehatan Kepada Remaja Melalui Aplikasi Android Profoteen - Sudiarto Sudiarto; Fayruz Zahrotin Niswah; Rizka Eka Putri Pranoto; Iffah Hanifah; Aprilia Aldila Enggardini; Zumrotul Masruroh; Hayyan Nazri Adlani Muhammad (Jurnal Kepemimpinan dan Manajemen Keperawatan, 2019)
The adolescent is at risk of having unhealthy behaviors such as premarital sex, which will result in the occurrence of pregnancies, abortions, and sexually transmitted diseases (STDs). One of these technological advances is information technology (IT) which has applied in various aspects of human life. Technology information is important for the millennial generation, one of which is inseparable from the use of smartphones. Â The objectives of this review are identifying and develop an android-based educational application so that teenagers can use the technologies to knowledge especially about the reproductive health of girls in an attractive manner with existing features. The literature review refers to 5 articles obtained from e Pubmed, Undip E-journal, and Google Scholar databases over the past 5 years. Keywords in article search are mobile application, education, reproductive health, adolescent knowledge, health, and smartphone applications. Data analysis techniques that have been done are compare, contrast, criticize, syntesize and summarize. Inclusion criteria for articles are scientific articles with the last 5 years publication period, reliable and accredited articles, types of original research articles, and case studies. The exclusion criteria are undergraduate student research articles. From the literature study shows that those applications are much helpful in reducing problems that often occur in adolescents, for example: The Girl Talk application significantly increases the knowledge of adolescent girls (35.3% vs. 94.1%; p <0.001) respectively. Each application has a positive impact on improving adolescent health.